Feeding rate of red tilapia (Oreochromis niloticus mossambicus) and correlation between feed intake and water quality - Jongjaraunsuk, Roongparit; Is-haak, Jesada; Taparhudee, Wara (RMUTSB ACADEMIC JOURNAL, 2019)
This study investigated the feeding rate and correlation between feed intake (FI) and water quality parameters of red tilapia cage culture suspended in earthen ponds. The first experiment conducted in laboratory condition to investigate the feeding rate and the results show that the feeding rates in the laboratory of fish sizes 100, 200, 300, 400, 500, 600, 700 and 800 g were 3.61±0.22, 3.22±0.43, 2.72±0.35, 2.59±0.22, 2.27±0.11, 2.24±0.05, 2.15±0.04 and 2.07±0.04% of their body weight, respectively. The second experiment was performed in outdoor cages suspended in earthen ponds conditions. There was a negative relationship between total ammonia nitrogen (TAN) level in the pond water on FI and average daily gain (ADG). Whenever TAN level was higher than 0.5 mg L-1, FI and ADG would decrease.